Relationship between self-disclosure and anticipatory grief in patients with advanced lung cancer: the mediation role of illness uncertainty - Zhang, Nan; Li, Han; Kang, Huaxin; Wang, Yinglan; Zuo, Zhitong (Frontiers in Psychology, 2023)
Objective To study the relationship between self-disclosure, illness uncertainty (IU) and anticipatory grief (AG) in patients with advanced lung cancer. Methods This is a cross-sectional study using convenience sampling method, in which 316 patients with advanced lung cancer who were hospitalized in a tertiary hospital in Wuxi City, China, from November 2022 to April 2023 were sampled. The Preparatory Grief in Advanced Cancer Patients, Mishel Uncertainty in Illness Scale, and the Distress Disclosure Index Scale (DDI) were selected to analyse the status quo, correlations, and the mediating effect of illness uncertainty on the relationship between self-disclosure and anticipatory grief in advanced lung cancer patients. Results The total self-disclosure score of advanced lung cancer patients was (36.35 ± 9.25), the total score of IU was (56.92 ± 15.65), and the score of AG was (52.29 ± 9.08); the results of correlation analyses showed that IU was negatively correlated with self-disclosure in advanced lung cancer patients (p < 0.05) and positively correlated with AG (p < 0.05), and self-disclosure was negatively correlated with AG (p < 0.05);the mediating effect rate of IU between self-disclosure and AG in advanced lung cancer patients was 49%. Conclusion The AG of advanced lung cancer patients was at a medium-high level, and IU had a significant mediating effect between self-disclosure and AG of advanced lung cancer patients; by increasing the level of patients’ self-disclosure, IU could be effectively alleviated, and ultimately the AG of the patients could be reduced.